Who's running this ecosystem? Proceedings of the 13th annual South Platte forum - Brown, Jennifer, editor; Colorado Water Resources Research Institute, publisher (Colorado State University. Libraries, 2002)
Abstracts of papers presented at the 13th annual South Platte Forum held on October 23-24, 2002 in Longmont, Colorado.
Abstracts of papers presented (47 pages)
Keywords: Watershed management -- South Platte River Valley (Colo. and Neb.) -- Congresses; Ecosystem management -- South Platte River Valley (Colo. and Neb.) -- Growth -- Congresses; Water use -- South Platte River Valley (Colo. and Neb.) -- Congresses; Water resources development -- South Platte River Valley (Colo. and Neb.) -- Congresses